A world without princes - Chainani, Soman; Bruno, Iacopo (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2014)
When best friends Sophie and Agatha return to a fairy tale world, they find that old enemies are no longer fighting, but a war begins to brew as an enemy arises from within.
Ages 8-12.
Keywords: Best friends -- Juvenile fiction; Schools -- Juvenile fiction; Good and evil -- Juvenile fiction; Best friends -- Fiction; Schools -- Fiction; Good and evil -- Fiction; Fantasy